Type and authentic specimens of Agropyron Gaertn. and Elytrigia Desv. taxa (Poaceae) in the Нerbarium of V.N.Karazin Kharkiv National University (CWU) - Гамуля, Ю. Г.; Сіра, О. Є. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The article lists the type and authentic herbarium material of valid and non-valid taxa (species and forms) of the genera Agropyron G. Gaertn. and Elytrigia Desv. (Poaceae), those are currently stored in the Herbarium of the Kharkiv National University (CWU). Among them: Elytrigia сretacea Klokov et Prokudin, E. lolioides (Kur. et Kir.) Newski var. cretacea Prokudin, E. maeoticа Prokudin, E. pseudocaesia (Pacz.) Prokudin, E. ruthenica (Griseb.) Prokudin, E. prokudinii Drul., E. ruthenica (Griseb.) Prokudin var. czurjukiense Prokudin, Agropyrum baicalense W. Drobow, A. brandzae Panţu & Solacolu, A. dasyanthum Ldb. var. giganteum Prokudin, A. dasyanthum Ldb. f. mucronata Prokudin, A. dasyanthum Ldb. f. pseudotanaitica Prokudin, A. dasyanthum Ldb. ssp. protodasyanthum Prokudin. f. pilіiglumis Prokudin, A. desertorum Fisch. var. dasyphyllum (Schr.) Roshev., A. imbricatum (M.B.) Roem. et Schult. var. hirticaulis Prokudin, A. lavrenkоanum Prokudin, A. ponticum Nevski, A. sibiricum (Willd) P.B. var. subaristatum Roshev. f. coryphyllum (Schr.) Roshev., A. sibiricum (Willd) P.B. var. dasyphyllum (Schr.) Roshev., A. prototanaiticum M. Klokov.